Removal of mercury(II), lead(II) and cadmium(II) from aqueous solutions using Rhodobacter sphaeroides SC01. (March 2020) - Su, Yan-Qiu; Zhao, Yang-Juan; Zhang, Wei-Jia; Chen, Guo-Cheng; Qin, Han; Qiao, Dai-Rong; Chen, Yang-Er; Cao, Yi
Abstract: Microorganisms and microbial products can be highly efficient in uptaking soluble and particulate forms of heavy metals, particularly from solutions. In this study, the removal efficiency, oxidative damage, antioxidant system, and the possible removal mechanisms were investigated in Rhodobacter (R.) sphaeroides SC01 under mercury (Hg), lead (Pb) and cadmium (Cd) stress. The results showed that SC01 had the highest removal rates (98%) of Pb among three heavy metals. Compared with Hg and Cd stress, Pb stress resulted in a lower levels of reactive oxygen species (ROS) and cell death. In contrast, the activities of four antioxidant enzymes in SC01 under Pb stress was higher than that of Hg and Cd stress. Furthermore, the analysis from fourier transform infrared spectroscopy indicated that complexation of Pb with hydroxyl, amid and phosphate groups was found in SC01 under Pb stress. In addition, X-ray diffraction analysis showed that precipitate of lead phosphate hydroxide was produced on the cell surface in SC01 exposed to Pb stress. Therefore, these results suggested that SC01 had good Pb removal ability by biosorption and precipitation and will be potentially useful for removal of Pb in industrial effluents. Graphical abstract: Image 1 Highlights: Among three heavy metals, mercury (Hg) stress resulted in the severe oxidative damage in R. sphaeroides SC01. The strain SC01 showed high removal efficiency of lead (Pb). Under Pb stress, the formation of precipitates of Pb phosphate hydroxide helped to improve the resistance to Pb and the removal rates of Pb in R. sphaeroides SC01.